2020
DOI: 10.1038/s41598-020-68573-3
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the changes in lower extremities related to progression of adult spinal deformity: a longitudinal study of over 22 years

Abstract: this longitudinal observational study investigated the relationship between changes in spinal sagittal alignment and changes in lower extremity coronal alignment. A total of 58 female volunteers who visited our institution at least twice during the 1992 to 1997 and 2015 to 2019 periods were investigated. We reviewed whole-spine radiographs and lower extremity radiographs and measured standard spinal sagittal parameters including pelvic incidence [pi], lumbar lordosis [LL], pelvic tilt [pt], sacral slope [SS] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Yasuda et al [4] reported there was poor sagittal spinopelvic alignment in knee osteoarthritis cases. Changes in PI-LL were associated with changes in FTA in over 22 years of follow-up as previously reported [19]. There were a few studies that reveal the relationship between DLS and coronal lower extremity alignment in elderly cases.…”
Section: Discussionsupporting
confidence: 82%
“…Yasuda et al [4] reported there was poor sagittal spinopelvic alignment in knee osteoarthritis cases. Changes in PI-LL were associated with changes in FTA in over 22 years of follow-up as previously reported [19]. There were a few studies that reveal the relationship between DLS and coronal lower extremity alignment in elderly cases.…”
Section: Discussionsupporting
confidence: 82%
“…The second study reported the proportion of patients with KOA having a concurrent mechanical diagnosis and therapy classification of spinal derangement [ 23 ]. The third study reported the correlation coefficients between changes in KL grade of the knee joint and lumbar spine [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine studies with 5,758 patients were included in this systematic review [16][17][18][19][20][21][22][23][24]: four cross-sectional studies, three prospective cohort studies, and two retrospective cohort studies. The study characteristics are summarized in Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate that trunk lean is associated with coronal knee moment [23][24][25][26]. The stress concentration from the spine to the lateral joint of the knee caused lateral 5 Case Reports in Orthopedics Subsequently, it was discovered that apart from the adjacent hip joint, the knee joint equally affects spinal alignment [27][28][29]. In recent years, the syndrome is called knee-hipspine syndrome [30].…”
Section: Discussionmentioning
confidence: 99%